Sintesis dan karakterisasi sifat optik film tipis hausmannite (Mn3O4) dengan metode spin coating ( Synthesis and characterization of the optical properties of hausmannite thin film (Mn3O4) by spin coating method ) - Bevi Lidia; - Ratnawulan; - Ramli (PILLAR OF PHYSICS, 2018)
Hausmannite is applied as a semiconductor electronics material one of them as optoelectronic material. The purpose of this research is to investigate the influence of calcination temperature on the growth of thin film by spin coanting method against the optical properties of hausmannite. Based on the results of the value of transmittance and reflectance of the thin film of hausmannite decreases at a temperature of 200 °C to 400 °C then enlarges at a temperature of 500 °C. And the absorbance value of the thin film of hausmannite enlarges at a temperature of 200 °C to 400 °C and then shrinks at a temperature of 500 °C. Using the value of transmittance obtained large energy gap at the temperature calcination 200 °C, 300 °C, 400 °C and 500 °C is 1.53 eV, 1.64 eV, 2.26 eV and 2.28 eV.